Corynebacterium imitans sp. nov. isolated from patients with suspected diphtheria. - Funke, G (1997)
A 5-month-old boy of a Romanian family traveling via Ukraine to Poland developed a respiratory disease that resembled and that was initially diagnosed as pharyngeal diphtheria. The child recovered after treatment with antidiphtheria antitoxin. A coryneform bacterium had been isolated from a nasopharyngeal specimen from the child and was initially identified as an atypical Corynebacterium diphtheriae strain. Seven adults who had contact with either the child or an adult contact person also developed symptoms of pharyngeal diphtheria, were also treated with antitoxin, and recovered uneventfully. Coryneform bacteria similar to that originating from the index patient were also isolated from the throat swabs of three adults. Detailed biochemical and chemotaxonomic investigations revealed that the coryneform bacteria belonged to the genus Corynebacterium and could be differentiated from all other defined species of this genus. Ribotyping and pulsed-field gel electrophoresis demonstrated that all four patients' isolates were of clonal origin. The diphtheria toxin gene and its product were not detected either by PCR assays or by the Elek test, making a possible disease association of the Corynebacterium more unlikely. Comparative 16S rRNA gene sequence analysis revealed that the coryneform bacterium represented a new subline within the genus Corynebacterium, for which the name Corynebacterium imitans sp. nov. is proposed. The type strain is NCTC 13015 (DSM 44264; CCUG 36877).